Collaboration between teachers and educational-psychological service counsellors. (June 2023) - Jortveit, Maryann
This qualitative study examines cross-professional collaboration between Educational-Psychological Service (EPS) counsellors and school teachers who have pupils with special needs in their class. Research shows that EPS counsellors spend much time writing assessment reports, that they do not have much presence in school and that there is a power imbalance between the collaborating parties. The collaboration may be experienced as imbalanced because the teacher is dependent on the EPS counsellors' expertise and assessment reports for special teaching resources to be made available for pupils. Six teachers have been interviewed about their collaboration with EPS staff. The thematically analysed findings show that the teachers generally have good collaboration with the counsellors and trust them. However, they feel vulnerable because their teaching is being assessed, and they depend on the EPS report's recommendations for resources. The informants feel that the typical signs of an equal collaboration relationship are when the partners have a good dialogue and mutual trust. A role clarification between the collaboration parties is needed, where there is trust, acknowledgement and mutual respect. This will in turn inspire a collaboration that leads to changes in the teaching situation and to special teaching measures for the pupils with special needs.